The Bank Choice Behaviour Among Malaysian Muslims: A Qualitative Approach - Ahmad Azrin, Adnan; Noor Azeanti, Mohd Nasir (2014)
This paper aims to understand the key motivations for Islamic bank patronage among Muslims using in-depth interviews and non-participant observation. This research used in-depth interviews and non-participant observation of Muslim customers of Islamic banks located in Terengganu, the earliest state to receive Islam in Malaysia and is well-known in adopting the Islamic governance system. 15 customers were determined to comprise the resultant sampling frame. The identified factors developed the four themes of customer profiling: i. ability (taufeeq) and guidance (hidayah); ii. guidance (hidayah) without ability (taufeeq); iii. ability (taufeeq) without guidance (hidayah); and iv. no ability (taufeeq) and guidance (hidayah). The “completeness of prayer” factor is a new discovery that could lead consumers to demonstrate an ideal behaviour according to Islamic teachings. Thus, the actual problem of the Islamic banking system especially among Muslims community is not the availability of shariah-compliant products or services, but the lack of shariah-adherent behaviour among Muslims